The ethical frontiers of biotechnological applications - Girón Morazán, Gladys (2019)
This article, tries to reflect on the ethical implications and why not say it moral that involves biotechnological progress in the life of the human being and therefore the impact that occurs in culture, in society. For this, it is necessary to become aware of the importance of ethics in society, only by recognizing the true value and the real dignity that the person possesses, technique and science will have the right place and with it the borders of Ethics in biotechnological applications will be clear. Nowadays it is of the utmost importance to make this reflection since the scientific and technical progress is made more quickly and once discovered, the next step would be to apply it, the detail is that this application is not made in something, but in “someone” , which is why ethical dialogue and debate must be governed fundamentally by the principles: respect for human life and self-determination of the human person; In addition to the rules, in the matter of scientific research and health care lies in human dignity; This dignity of man lies in his personal being, has understanding, will, freedom and awareness of his actions, self-determination, self-realization and self-awareness. Taking into account these principles and their rules, ethical judgments may be issued on current issues such as everything related to genetic manipulation in which the manipulation of genetic data, gene therapy, biological products for therapeutic use come into play with the corresponding pharmacology that is being developed, cloning, hybrid embryos, transgenic foods, among others. On the other hand we have the issues regarding the environment and its ecology to combat, reduce and eliminate environmental pollution and that in one way or another can affect the life of the human being.